- The factors affecting the evaluation and selection of hotels - An analytical study of a field a sample of tourists visiting the State of Djelfa - Algeria - Toual, Hiba Ali; Mahamdi, Siham Salem (Journal of Economic, Administrative and Legal Sciences, 2020)
This research aims to study the impact of a range of factors on the evaluation and selection of hotels, for that we’ve conducted a study based on the descriptive analytical approach, where 100 questionnaires were distributed to a random sample of tourists visiting the state of Djelfa- Algeria. The study found that the evaluation and selection of the hotel within the sample members is influenced by the range of factors covered by the study (the purpose of the visit, the definition of value by the visitor, the social and economic factors, age and gender, race or religion). Depending on the correlation coefficient value (R 0.885), the relationship between the independent variable and the dependent variable was strong, and the independent variable explains 77.2%of the dependent variable. Finally, the study has presented a set of recommendations, which conclude in:- Renovation and development of the interior design of hotels;- Annual training programs including the hotel staff and this is to learn about new trends in the hotel’s industry.